The sensitivity of nocturnal low‐level jets and near‐surface winds over the Sahel to model resolution, initial conditions and boundary‐layer set‐up. (28th October 2014) - Schepanski, K.; Knippertz, P.; Fiedler, S.; Timouk, F.; Demarty, J.
<x xml:space="preserve">Abstract</x> This study explores simulations using the numerical Weather Research and Forecasting (WRF) model, with respect to the representation of the nocturnal low‐level jet (LLJ) over the Sahel. Three sets of experiments are designed to investigate the sensitivity with respect to (i) the boundary‐layer and surface‐layer schemes including local and non‐local closures, (ii) the horizontal grid spacing and the number of vertical levels within the lowest kilometre and (iii) the role of initial and boundary data. In total, 27 simulations are performed on one host domain and two nested domains for a representative LLJ case study on 9 November 2006. The ability of the individual simulations to represent the life cycle of the nocturnal LLJ is validated against observations carried out in the framework of the African Monsoon Multidisciplinary Analysis (AMMA) special observation periods: surface wind observations from Agoufou, Bamba and Banizoumbou, atmospheric wind profiles derived from Atmospheric Radiation Measurement Mobile Facility, wind radar measurements at Niamey and profiles from radiosondes launched at Niamey. All runs reproduce the general characteristics of the observed LLJs satisfactorily. In contrast to earlier studies, results are more sensitive to the choice of initial and boundary data (here GFS and ECMWF) than to the boundary‐layer and surface schemes used or to model grid resolution. The sensitivity to the model grid resolution is surprisingly minor. Considerable differences between the individual stations suggest that local surface conditions such as roughness length, albedo or soil moisture may play an important role in the observed mismatch between model simulations and observations.